For Kids in the Hospital, Video Games Are Part of Recovery - Schriefer, Natalie (Wired, 2022)
In-house gaming technology specialists play with and support the youngest patients. Plus, research shows that playtime gives literal health points.
Keywords: charity; dept.hhs; gaming culture; health care; video games